2016
DOI: 10.1016/j.visres.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

A proto-object based saliency model in three-dimensional space

Abstract: Most models of visual saliency operate on two-dimensional images, using elementary image features such as intensity, color, or orientation. The human visual system, however, needs to function in complex three-dimensional environments, where depth information is often available and may be used to guide the bottom-up attentional selection process. In this report we extend a model of proto-object based saliency to include depth information and evaluate its performance on three separate three-dimensional eye track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Slowness prototypes in ventral stream (Yousefi & Loo, 2015) . proto-object based on the saliency map (Hu et al 2016) . Coupling complex optical flows (Casile&Giese, 2005) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slowness prototypes in ventral stream (Yousefi & Loo, 2015) . proto-object based on the saliency map (Hu et al 2016) . Coupling complex optical flows (Casile&Giese, 2005) .…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of this hypothesis includes brain image studies and examination of the functional segregation light of the perceptual mechanisms subtending visual recognition and the same mechanism used for action [51]. Same methodology with slight extension used for proto-object model based on the saliency map, which involved depth information using the 3D eye tracking datasets presented by Hu et al (2016) [52], which was followed the evidence that supports the influence of eye movements on shape processing in the human visual system [6].…”
Section: Structural Methodsmentioning
confidence: 99%
“…In past studies, researchers have used binocular disparity to define the depth of different elements on discrete planes across the z-axis of the display (de la Rosa et al, 2008;Hu, Kane-Jackson, & Niebur, 2016;Marrara & Moore, 2000;Moore, Elsinger, & Lleras, 2001;Nakayama & Silverman, 1986;O'Toole & Walker, 1997). These studies have shown that attention can be focused at a particular depth;…”
Section: Discussionmentioning
confidence: 99%
“…Recent physiological studies reported that the cortical representation of 3D objects is mediated by 3D surface and 3D medial axis in monkey visual area IT ( Yamane et al, 2008 ; Hung et al, 2012 ). It might be interesting if those 3D representations were generated directly from the local BO signals ( Hu et al, 2016 ). This might be in line with the point that occlusion seems to be the most effective cue in the determination of the order of 3D depth.…”
Section: Discussionmentioning
confidence: 99%